Whole exome sequencing reveals de novo pathogenic variants in KAT6A as a cause of a neurodevelopmental disorder. Issue 7 (2nd May 2016) - Millan, Francisca; Cho, Megan T.; Retterer, Kyle; Monaghan, Kristin G.; Bai, Renkui; Vitazka, Patrik; Everman, David B.; Smith, Brooke; Angle, Brad; Roberts, Victoria; Immken, LaDonna; Nagakura, Honey; et al.
Abstract : Neurodevelopmental disorders (NDD) are common, with 1–3% of general population being affected, but the etiology is unknown in most individuals. Clinical whole‐exome sequencing (WES) has proven to be a powerful tool for the identification of pathogenic variants leading to Mendelian disorders, among which NDD represent a significant percentage. Performing WES with a trio‐approach has proven to be extremely effective in identifying de novo pathogenic variants as a common cause of NDD. Here we report six unrelated individuals with a common phenotype consisting of NDD with severe speech delay, hypotonia, and facial dysmorphism. These patients underwent WES with a trio approach and de novo heterozygous predicted pathogenic novel variants in the KAT6A gene were identified. The KAT6A gene encodes a histone acetyltransfrease protein and it has long been known for its structural involvement in acute myeloid leukemia; however, it has not previously been associated with any congenital disorder. In animal models the KAT6A ortholog is involved in transcriptional regulation during development. Given the similar findings in animal models and our patient's phenotypes, we hypothesize that KAT6A could play a role in development of the brain, face, and heart in humans. © 2016 Wiley Periodicals, Inc.